2013
DOI: 10.5152/eajm.2013.03
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Risk Factors of Human Papillomavirus in Female Sex Workers

Abstract: Objective: Human papillomavirus virus (HPV) is the major causative factor for cervical cancer, and sex workers are at high risk for HPV infection. In this study, we aimed to estimate the prevalence and risk factors of HPV infection among female sex workers (FSWs). Materials and Methods:The study included 239 brothel-based FSWs who work in Izmir, Turkey. A self-administered questionnaire for risk factors was completed, and cervical brush samples were taken for HPV detection and typing. HPV detection and typing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…In Turkey not many studies are carried out in this regard. In a study performed in Izmir HPV prevalence in FSWs was found as 20.1%, while in another study carried out in Turkey it was reported as 13% 22,23 . In our study, 56.3% and 53.4% of FSWs reported having heard of HPV and HPV vaccination, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…In Turkey not many studies are carried out in this regard. In a study performed in Izmir HPV prevalence in FSWs was found as 20.1%, while in another study carried out in Turkey it was reported as 13% 22,23 . In our study, 56.3% and 53.4% of FSWs reported having heard of HPV and HPV vaccination, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…[6,7] The second peak has been associated with factors that may be due to HPV types, host propensity, and previous screening programs. [6,8] Alternatively, some literature studies have indicated that the prevalence of a second peak related to age is decreasing. [1,7,8,18] In our study, HPV prevalence was higher in age the groups of those younger than 30 and older than 55 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…[6,8] Alternatively, some literature studies have indicated that the prevalence of a second peak related to age is decreasing. [1,7,8,18] In our study, HPV prevalence was higher in age the groups of those younger than 30 and older than 55 years of age. Our study was the first in this country to demonstrate a bimodal age distribution.…”
Section: Discussionmentioning
confidence: 99%
“…23 Penelitian Ersan di Turki pada tahun 2013 didapatkan 62% WPS adalah perokok aktif. 25 Hal yang berbeda didapatkan pada penelitian Tideman di Sydney pada tahun 2003 dimana hanya 56% WPS-L di Sydney merupakan perokok aktif. 26 Penelitian Odukoya di Nigeria pada tahun 2013 didaptkan 72% WPS tidak pernah merokok.…”
Section: 18unclassified